An assessment of treatment of migraine/headache syndrome in patients seen in private practice - Fox, Anthony Dunstan (British Homeopathic Journal, 1990)
Fifty-four patients suffering from headache/migraine syndrome as well as other symptoms who had consulted me approximately 18 months previously and were treated by diet and homœopathy were sent a questionnaire to assess their progress. Forty-three replied—of these 35 did well and enjoyed improvement in their symptoms in the first four weeks after the first consultation. Thirty-five still keep moderately well to date.
Keywords: Migraine; Headache; Private practice; Questionnaire; Homœopathy; Exclusion diet; Vegatest